2015
DOI: 10.1016/j.nbd.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Parallel age-associated changes in brain and plasma neuronal pentraxin receptor levels in a transgenic APP/PS1 rat model of Alzheimer's disease

Abstract: Neuronal pentraxin receptor (NPR) is a synaptic protein implicated in AMPA receptor trafficking at excitatory synapses. Since glutamate neurotransmission is disrupted in Alzheimer’s disease (AD), NPR levels measured from plasma represent a potential biomarker for synaptic dysfunction associated with AD. We sought to determine the relationship between AD pathology and brain and plasma NPR levels by examining age-associated NPR levels in these compartments in a transgenic APP/PS1 rat model of AD. NPR levels in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In particular, marked deficits are seen by 18–20 months of age (Bilousova et al, 2015). Average swim latencies for the two treatment groups at 17–18 months of age across 10 days of training trials are shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, marked deficits are seen by 18–20 months of age (Bilousova et al, 2015). Average swim latencies for the two treatment groups at 17–18 months of age across 10 days of training trials are shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 99%
“…NP1 negatively regulates mitochondrial function, transport and caspase activation through (Clayton et al, 2012) and negatively regulates excitatory synapse density (Figueiro-Silva et al, 2015). Since the expression of neuronal pentraxins is disrupted in AD brain and AD animal models (Abad et al, 2006, Bilousova et al, 2015, Cummings et al, 2017, Neuner et al, 2017, we investigated whether NP1 might serve as excitatory synapse derived plasma biomarker that is related to Aβ and/or apoE isoform effects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…NP1 and its fragments are upregulated in the brain and plasma of 7-8-month-old E4FAD mice (a transgenic mouse model of familial AD using APOE4 genotype), in 4 month-old WT mice with induced αβ burden, and in the plasma of patients with mild cognitive impairment (Ma et al, 2018). Interestingly, NPR is upregulated in soluble cortical homogenate fractions of 3-9-month-old APP/PS1 rats, but not at 18-20 months (Bilousova et al, 2015). The suggestion is that the lack of soluble NPR in the late-stage animals was due to a degradation in TACE activity (Qian et al, 2016) leading to less cleaved NPR in the soluble preparations.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…TACE (or ADAM17), the cleavage enzyme of NPR, is also able to act as an α-secretase for APP, resulting in a proposed neuroprotective by-product (Postina, 2012). TACE is also upregulated in AD (Skovronsky et al, 2001) but becomes inactive in the later stages of AD as the αβ burden increases (Bilousova et al, 2015). It could be that TACE is upregulated to combat the growing concentration of APP or in response to the increase in APP (Lüscher and Huber, 2010).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation